Neuropsychological functioning and psychosocial outcome in adults with attention-deficit/ hyperactivity disorder - Sobanski, Esther; Banaschewski, Tobias (Zeitschrift für Neuropsychologie, 2015)
This study explores the association of neuropsychological functioning with ADHD-symptoms and psychosocial functioning in a clinical sample of 131 adults with ADHD. Neuropsychological functioning was assessed with the computerized Test Battery of Attentional Performance (TAP). Overall psychosocial impairment was assessed with the Global Assessment of Functioning Scale (GAF). Neuropsychological performance was impaired in 39.6 % of the ADHD-patients meeting a predefined impairment criterion of a perfomance reduction of 1.5 standard deviations below normative controls in ≥ 2 TAP-subtests; 28.4 % of the patients showed regular performance in all neuropsychological tests. Severity of neuropsychological impairment was inversely correlated to severity of psychosocial impairment (GAF score; = -.24, p < .001) but not to childhood or adult ADHD symptoms. Overall severity of neuropsychological impairment explained 10 % (p < .05) of variance of psychosocial impairment.